An interpretive use of drawings to explore the lived experiences of orphaned children living with HIV/AIDS in South Africa - Steenveld, Clint Michael (Rhodes University, Faculty of Humanities, Department of Psychology, 2004)
Against the backdrop of the growing problem of AIDS orphans in South Africa and greater sub-Saharan Africa, this qualitative enquiry examines the lives of three South African orphaned children living with HIV / AIDS in a children's home in Cape Town. It aims to generate rich, child-centred descriptions of some of the significant experiences of the children's lives. Drawings, dialogue and narrative were employed to generate the primary data. This was supplemented by collateral interviews and other relevant records, e.g. medical and biographical. Existential-phenomenological theory informed the approach to data collection and analysis. Each child produced a series often to twelve impromptu drawings over a period often weeks. These drawings and transcripts of the children's verbal descriptions of their drawings were extensively analysed. Significant themes for each participant as well as themes common to all three were identified. Some of the central themes emerging include loss, abandonment, death, disease awareness and coping. The children's ability to develop adaptive coping mechanisms and resilience in the face of traumatic loss and terminal illness was a particularly outstanding feature of the findings. Recommendations are made regarding future research to address the lack of qualitative, child-focused investigations as well as appropriate interventions for addressing the psychosocial needs of orphaned children living with HIV/AIDS.
Keywords: AIDS (Disease) -- South Africa AIDS (Disease) -- Social aspects -- South Africa; HIV infections -- South Africa HIV infections -- Social aspects -- South Africa; AIDS (Disease) -- Psychological aspects; HIV infections -- Psychological aspects -- South Africa; AIDS (Disease) in children -- Psychological aspects -- South Africa